Minipuberty assessment in newborns with hypoxic ischemic encephalopathy treated with therapeutic hypothermia: a single-center case–control study - Lanciotti, Lucia; Sica, Rossella; Penta, Laura; Parisi, Francesca; Argentiero, Alberto; Radicioni, Maurizio; Di Cara, Giuseppe; Di Genova, Francesca; Verrotti, Alberto; Troiani, Stefania; Esposito, Susanna Maria Roberta (Frontiers in Pediatrics, 2023)
Introduction The aim of our single-center case–control study is to evaluate whether minipuberty occurs in patients with hypoxic ischemic encephalopathy (HIE) who underwent therapeutic hypothermia (TH). We intend to conduct this evaluation by confronting the values of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) and the values of testosterone in males and estradiol in females between newborns with HIE and in subsequent TH and healthy controls. Methods We enrolled 40 patients (age: 56–179 days; 23 males), of whom 20 met the inclusion criteria for the case group and who underwent TH. A blood sample was taken from each patient at approximately 10 weeks of age to evaluate FSH and LH from the serum samples of all patients and to evaluate 17-beta estradiol (E2) and testosterone levels, respectively, from the serum samples of female and male patients. Results It was found that minipuberty occurred in the case group patients, with no significant differences reported from the control group and with hormonal serum levels comparable to healthy infants of the control group (FSH 4.14 mUI/ml ± 5.81 SD vs. 3.45 mUI/ml ± 3.48 SD; LH 1.41 mUI/ml ±1.29 SD vs. 2.04 mUI/ml ±1.76 SD; testosterone in males 0.79 ng/ml ± 0.43 SD vs. 0.56 ng/ml ± 0.43 SD; 17-beta estradiol in females 28.90 pg/ml ± 16.71 SD vs. 23.66 pg/ml ± 21.29 SD). Discussion The results of the present study may pave the way for further research and the evaluation of more possible advantages of TH.